The Role of Microglia and Matrix Metalloproteinases Involvement in Neuroinflammation and Gliomas - Helen Könnecke; Ingo Bechmann (Clinical and Developmental Immunology)
Matrix metalloproteinases (MMPs) are involved in the pathogenesis of neuroinflammatory diseases (such as multiple sclerosis) as well as in the expansion of malignant gliomas because they facilitate penetration of anatomical barriers (such as the glia limitans) and migration within the neuropil. This review elucidates pathomechanisms and summarizes the current knowledge of the involvement of MMPs in neuroinflammation and glioma, invasion highlighting microglia as major sources of MMPs. The induction of expression, suppression, and multiple pathways of function of MMPs in these scenarios will also be discussed. Understanding the induction and action of MMPs might provide valuable information and reveal attractive targets for future therapeutic strategies.